Prevalence And Distribution Of Pneumonic Lesions In Goats - Verma, Anuradha; Swamy , Madhu; Shrivastava, Dharam Prkash (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted on prevalence and distribution of pneumonic lesions in goats. Total 97 cases were examined. Lung lesions were observed in 67.03% of goats. Detailed gross and microscopic study was conducted on fifty post mortem cases. 82% lungs were affected bilaterally. Gross examination revealed areas of emphysema, congestion, consolidation, pulmonary edema, pleural adhesion, lung abscess and nodular growth. Maximum number of bronchopneumonia was diagnosed followed by interstitial pneumonia and only a single case of granulomatous pneumonia. Maximum cases of pneumonia showed diffuse pattern of lesions and only ten cases were having a multifocal pattern of lung lesions along with solitary case of local extensive lesions. Histopathology was conducted on most affected lobe of lung. Microscopic changes corroborated with gross lesions in target organ.